1999
DOI: 10.1109/25.806786
|View full text |Cite
|
Sign up to set email alerts
|

A new method for reducing the power consumption of portable handsets in TDMA mobile systems: conditional equalization

Abstract: In time-division multiple-access (TDMA) systems, the autonomy of portable handsets is a major constraint. We propose a new method, conditional equalization, which minimizes the power consumption due to equalization by equalizing only when it is most needed. At each time slot, the receiver estimates the need for equalization with a deterministic criterion. The proposed criteria use thresholds, chosen to provide a compromise between loss in performance and percentage of saved equalization. The performance of our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…In determining the quality of the received signal, the authors do not specify whether the degradation of the signal is due to the intersymbol interference or to other phenomena, but they are relying on the total degradation. For the same reason of reducing energy consumption, [5] proposes a new method, called conditional equalization, which minimizes the power consumption by equalizing only when it is most needed. At each time slot, the receiver decides if the equalization is needed or not by de�ning two criteria in order to distinguish between weakly dispersive channels and dispersive channels in the case of a two-path Rayleigh channel.…”
Section: Previous Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In determining the quality of the received signal, the authors do not specify whether the degradation of the signal is due to the intersymbol interference or to other phenomena, but they are relying on the total degradation. For the same reason of reducing energy consumption, [5] proposes a new method, called conditional equalization, which minimizes the power consumption by equalizing only when it is most needed. At each time slot, the receiver decides if the equalization is needed or not by de�ning two criteria in order to distinguish between weakly dispersive channels and dispersive channels in the case of a two-path Rayleigh channel.…”
Section: Previous Workmentioning
confidence: 99%
“…Moreover, our work will be distinguished from the earlier works described above by the decision-making technique. In fact, we develop a technique that takes into account the uncertainty of the channel quality indicators' values used to decide to disable or keep the equalizer as they are estimated unlike the other techniques that ignore this aspect by assuming a perfect estimate of the metrics [5,6] or by not considering the impact of these uncertainties on the decision [7,8].…”
Section: Previous Workmentioning
confidence: 99%
“…This should reduce the computational complexity at the receiver. Related works from try to develop this idea of disabling the equaliser. Some of these previous works didn't have the purpose of reducing the energy consumption like in where the solution proposed increases, on the contrary, the energy consumption.…”
Section: Green Cognitive Radio Scenariomentioning
confidence: 99%
“…Some of these previous works didn't have the purpose of reducing the energy consumption like in where the solution proposed increases, on the contrary, the energy consumption. In and , the authors fixed a goal to reduce the consumption by limiting the presence of the equaliser. However, none of them has presented a study or an argument that justifies this reduction.…”
Section: Green Cognitive Radio Scenariomentioning
confidence: 99%
“…Previous studies have shown that conditional equalization can reduce power consumption by dynamically activating the equalizer or not, while not decreasing receiver performance [5].…”
Section: Introductionmentioning
confidence: 99%